Strategi Guru PAI dalam Meningkatkan Kedisiplinan Shalat di SMAN 1 Pare Kabupaten Kediri - Untung Khoiruddin (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
This article discusses the strategy of Islamic Religious Education teachers in improving the discipline of students at SMAN 1 Pare, Kediri Regency. SMAN 1 Pare, Kediri Regency, has a very strategic location, which is in the middle of the city crowd and facilities owned by the Kediri Regency Government. So that it can have an influence on the ethics and morals of students. So it is necessary to guide and educate Islamic Religious Education teachers in schools in terms of worship, especially discipline in carrying out prayers and other religious activities so that students' spiritual values increase and have noble character. This research was conducted using a descriptive qualitative approach and data collection methods through observation, interviews, and documentation. The results of the study reveal that: First, several strategies have been applied by Islamic Religious Education teachers in the form of (a) habituation from Islamic Religious Education teachers; (b) student discipline; (c) setting a good examples; (d) Providing advice and motivation; (e) Routinely invite students to the prayer room. Second, the supporting factors are (a) the spirit of Islamic Religious Education teachers; (b) SKI extracurricular activities; (c) its location is close to the grand mosque; (d) many religious activities in schools; (e) students' self-awareness. Third, while the inhibiting factors are (a) a small prayer room; no student data collection; (c) lack of prayer equipment; (d) time constraints; (e) cannot pray in congregation at the same time.